2007
DOI: 10.1001/archpsyc.64.10.1145
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Effects of Attention-Deficit/Hyperactivity Disorder, Conduct Disorder, and Sex on Adolescent Substance Use and Abuse

Abstract: Hyperactivity/impulsivity predicts later substance problems, even after growth in later-emerging CD is considered, whereas inattention alone poses less risk. Even a single symptom of ADHD or CD is associated with increased risk. Failure in previous research to consistently observe relationships between ADHD and substance use and abuse outcomes could be due to reliance on less-sensitive categorical diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
369
7
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(435 citation statements)
references
References 41 publications
50
369
7
9
Order By: Relevance
“…Likewise, Molina and colleagues (2003) found that ADHD, particularly inattention problems, did not correlate with adolescent substance use in the absence of conduct disorder. In contrast, Elkins et al (2007) found that hyperactive-impulsive symptoms continued to predict initiation of substance use, nicotine dependence, and cannabis use disorders, even after conduct disorder was controlled for.…”
mentioning
confidence: 75%
“…Likewise, Molina and colleagues (2003) found that ADHD, particularly inattention problems, did not correlate with adolescent substance use in the absence of conduct disorder. In contrast, Elkins et al (2007) found that hyperactive-impulsive symptoms continued to predict initiation of substance use, nicotine dependence, and cannabis use disorders, even after conduct disorder was controlled for.…”
mentioning
confidence: 75%
“…2 (Dependent) heavy cannabis use and mental healthP < 0.001), due possibly to the higher frequency of cannabis use in the present study. CD and childhood ADHD usually precede cannabis initiation, and both disorders predict cannabis use and cannabis dependence [50,51]. Therefore, this finding emphasizes the potential of targeted prevention in this high-risk group, as well as the importance of treating these childhood disorders to reduce the development of both frequent cannabis use and dependence.…”
Section: Mental Disordersmentioning
confidence: 88%
“…According to studies, these are all associated with the addictive behaviours in general [39,40]. For example, nicotine and alcohol use are positively associated with self-reported impulsivity symptoms [41] and increases in the number of impulsivity and conduct disorder (CD) symptoms are also associated with increased risk of other substance use disorders (SUDs) too [42]. There seems to be a similar pattern for Internet and SNSs addictions [43].…”
Section: Discussionmentioning
confidence: 99%